2002
DOI: 10.1897/1551-5028(2002)021<2698:acocfm>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Chelator-Facilitated Metal Uptake by a Halophyte and a Glycophyte

Abstract: Phytoextraction is the use of plants to remove contaminants, in particular metals, from soil via root uptake and translocation to the shoots. Efficient phytoextraction requires high-biomass plants with efficient translocating properties. Halophytes characteristically accumulate large quantities of salts in above ground tissue material and can have high biomass production. It has been speculated that salt-tolerant plants may also be heavy metal tolerant and, further, may be able to accumulate metals. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Chemical amendments that form watersoluble metal complexes, making metals more bioavailable for uptake by roots, have been identified as successful candidates to desorb metals from the soil matrix (Schmidt 2003). Chelating agents (Chiu et al 2005;Kulli et al 1999), organic acids (Chen et al 2003;Evangelou et al 2006), amino acids (Kerkeb and Kramer 2003;Singer et al 2007), synthetic and biosurfactants (Jordan et al 2002;Mulligan 2007), and inorganic ligands (Kayser et al 2000;Puschenreiter et al 2001) have been previously studied for enhancing bioavailability and metal accumulation in plant parts. However, only a limited number of phytoextraction studies have trialed combinations of amendments (Luo et al 2006a;Wu et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical amendments that form watersoluble metal complexes, making metals more bioavailable for uptake by roots, have been identified as successful candidates to desorb metals from the soil matrix (Schmidt 2003). Chelating agents (Chiu et al 2005;Kulli et al 1999), organic acids (Chen et al 2003;Evangelou et al 2006), amino acids (Kerkeb and Kramer 2003;Singer et al 2007), synthetic and biosurfactants (Jordan et al 2002;Mulligan 2007), and inorganic ligands (Kayser et al 2000;Puschenreiter et al 2001) have been previously studied for enhancing bioavailability and metal accumulation in plant parts. However, only a limited number of phytoextraction studies have trialed combinations of amendments (Luo et al 2006a;Wu et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is also exuded by plants into the soil and has been suggested as an alternative to synthetic chelators for use in chemically enhanced phytoextraction (Callahan et al 2005;Evangelou et al 2006). Rhamnolipid, an anionic biosurfactant produced by Pseudomonas aeruginosa, has been studied for complexation with heavy metals (Jordan et al 2002;Mulligan 2005;2007;Mulligan et al 2001;Ochoa-Loza et al 2001;Torrens et al 1998), remediation of heavy metal contaminated soils (Jordan et al 2002;Mulligan 2005;2007;Mulligan et al 2001;Ochoa-Loza et al 2001;Torrens et al 1998) and for use in phytoremediation (Johnson et al 2009, Jordan et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Glenn et al (1999) showed that Atriplex nummularia can achieve biomass yield of 20-30 t ha -1 year -1 and can accumulate up to 40% NaCl in its dry matter. Recent studies suggest that halophytes may be useful for phytoremediation of salty soils contaminated with heavy metals (Glenn et al 1999;Williams et al 1994;Jordan et al 2002;Ló pez-Chuken and Young 2005;Ghnaya et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Halophytic plants grow naturally in saline environment in many arid and semi-arid regions around the world and are distributed from coastal areas to mountains and deserts. Halophyte species can be irrigated with saline water and can also tolerate drought, freezing and heat (Thomas et al, 1998;Jordan et al, 2002;Lutts et al, 2004). Halophytic plants have many uses: They can be used as animal feeds, vegetables, and drugs, as well as for sand dune fixation, wind shelter, soil cover, cultivation of swampy saline land and paper production (El Shaer and Attia-Ismail, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Among the halophyte flora, species belonging to the genus Atriplex may be of special interest because of their high biomass production associated with a deep root system able to cope with the poor structure and xeric characteristics of several soils (Thomas et al, 1998;Jordan et al, 2002;Lutts et al, 2004). Atriplex (saltbush) species are characterized by good forage production, adaptation to living in environments affected by desertification, especially in arid areas, their applicability for restoration of rangelands, preventing erosion and protecting wildlife, fuel usage, tolerance to salinity and harsh environmental conditions (Mousavi Aghdam, 1986;Le Houerou 1992, 1995Walker et al, 2014).…”
Section: Introductionmentioning
confidence: 99%